Digital Trail Awareness in Islamic Perspective - Gunawan Adnan; Mulkan Fadhli; Farid Fathony Ashal (Elkawnie, 2021)
Abstract: The growing popularity of the internet has a significant impact on people's attitudes. The Covid-19 pandemic has accelerated a cultural, ethical, and normative change in people's behavior. The potential for social change resulting from the emergence or advancement of information and technology is significant. The rise of social media, which has now become a common form of communication, is unavoidable. Digital communication through a variety of websites to obtain information will leave digital traces. The concept of a digital trail certainly reaffirms what has previously been written in Al-Qur'an, Surah Yasin: 65. This verse is relevant to digital multi-hop tracks that outline human actions and behavior to the swipe of their fingers. The verse is translated through the use of a digital trail that is connected to internet access. This library research study uses the source triangulation method to analyse exploratory qualitative content. The study's findings indicate a correlation between the digital trail and Surah Yasin 65, demonstrating that current digital technology proves that the Qur'an's nash or verses are consistent with the unquestionable assumption of human rationality. It also emphasizes the importance of being cautious and responsible when using digital platforms.Abstrak: Tren peningkatan penggunaan internet memberikan pengaruh besar terhadap perilaku masyarakat. Pandemi Covid-19 mengakselerasi pergeseran pola perilaku masyarakat baik dari segi budaya etika maupun norma yang ada. Potensi terjadinya perubahan sosial sebagai konsekuensi lahir atau berkembangnya teknologi informasi sangat besar. Kemunculan media sosial yang kini sudah menjadi hal yang umum dalam berkomunikasi memang tak dapat dihindarkan lagi. Jalur komunikasi di era digital yang melalui berbagai proses untuk mendapatkan informasi akan meninggalkan jejak-jejak digital atau digital footprint. Potret jejak digital ini tentunya menegaskan kembali apa yang telah dituliskan dalam Al Quran pada surah Yasin ayat 65. Ayat ini memiliki relevansi dengan jejak hop digital menguraikan perbuatan dan perilaku manusia dari sentuhan jari. Ayat tersebut diterjemahkan dengan footprint digital yang terhubung dalam sebuah jaringan internet. Studi ini merupakan library research dengan  pendekatan kualitatif explanatif dalam bentuk konten analisis dengan metode tringalasi sumber. Hasil studi menunjukkan bahwa terdapat korelasi digital footprint dengan Surah Yasin 65 di mana teknologi digital saat ini menjadi bukti bahwa nash yang termuat dalam Alquran sesuai dengan asumsi rasionalitas manusia yang tidak memiliki keraguan di dalamnya. Penekanan berikutnya adalah setiap individu harus cermat dan bertanggungjawab dalam mengakses platform digital.